Breaking the Dogma of Aldolase Specificity: Simple Aliphatic Ketones and Aldehydes are Nucleophiles for Fructose‐6‐phosphate Aldolase. Issue 21 (29th March 2017) - Roldán, Raquel; Sanchez‐Moreno, Israel; Scheidt, Thomas; Hélaine, Virgil; Lemaire, Marielle; Parella, Teodor; Clapés, Pere; Fessner, Wolf‐Dieter; Guérard‐Hélaine, Christine
Abstract: d ‐Fructose‐6‐phosphate aldolase (FSA) was probed for extended nucleophile promiscuity by using a series of fluorogenic substrates to reveal retro‐aldol activity. Four nucleophiles ethanal, propanone, butanone, and cyclopentanone were subsequently confirmed to be non‐natural substrates in the synthesis direction using the wild‐type enzyme and its D6H variant. This exceptional widening of the nucleophile substrate scope offers a rapid entry, in good yields and high stereoselectivity, to less oxygenated alkyl ketones and aldehydes, which was hitherto impossible. Abstract : Novelty from promiscuity : Fructose‐6‐phosphate aldolase (FSA) is famous for being the only aldolase that is able to convert different nucleophiles bearing an alpha‐hydroxylated carbonyl group. Here, a hidden activity was uncovered: FSA can also catalyze aldol additions of aliphatic nucleophiles such as propanone, ethanal, butanone, and even cyclopentanone, to glyceraldehyde 3‐phosphate thereby providing a stereoselective access to novel aldol adducts.